Khuruj Jamaah Tabligh Nunukan: Antara Dakwah dan Pemenuhan Nafkah - Jawahir, Muhamad; Andaryuni , Lilik (Universitas Pahlawan Tuanku Tambusai, 2025)
This research examines the practice of khuruj fisabilillah conducted by Jamaah Tabligh in Nunukan Regency and their efforts to fulfill family livelihood during these activities. Using empirical field research methods and a descriptive-analytical approach, this study aims to understand the stages that Jamaah Tabligh members must go through before implementing khuruj fisabilillah and how they fulfill their family's financial obligations during the khuruj period. Data was collected through observation and interviews with Jamaah Tabligh members in Nunukan Regency. The research findings show that before conducting khuruj, Jamaah Tabligh members must go through preparation and examination stages covering five aspects of tafaqqud: deeds, wealth, family, work, and health. Regarding livelihood fulfillment, members prepare well in advance of departure through savings and calculations of daily family needs. This research concludes that Jamaah Tabligh members continue to fulfill their family's financial responsibilities while carrying out khuruj fisabilillah by maintaining a balance between these two obligations.